PEMBELAJARAN INKUIRI TERBIMBING BERBANTUAN MEDIA SMART TV DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA DI SEKOLAH DASAR - Handoko Aji Wardana Handoko Aji Wardana; Sigit Arvianto; Nurhayati (LPPM Universitas Cipta Mandiri, 2026)
This study aimed to determine the effect of the guided inquiry learning model assisted by Smart TV media on the conceptual understanding of fifth-grade students at SD Islam Losari Lor. The research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The sample consisted of 34 students divided into two groups: an experimental class and a control class, each comprising 17 students. The experimental class was taught using the guided inquiry learning model supported by Smart TV media, while the control class received conventional instruction. Data were collected through a conceptual understanding test administered before and after the treatment. The results showed that the average posttest score of the experimental class was higher than that of the control class. These findings indicate that the implementation of the guided inquiry learning model assisted by Smart TV media had a positive effect on improving students’ conceptual understanding. Learning activities that involve inquiry stages and interactive visual media encourage active participation and help students construct concepts more meaningfully. Therefore, the guided inquiry learning model assisted by Smart TV media can be considered an effective alternative for elementary school learning.